2022
DOI: 10.1503/jpn.220102
|View full text |Cite
|
Sign up to set email alerts
|

Reduced signal propagation elicited by frontal transcranial magnetic stimulation is associated with oligodendrocyte abnormalities in treatment-resistant depression

Abstract: Background:The efficacy of repetitive transcranial magnetic stimulation (rTMS) to the left dorsolateral prefrontal cortex (dlPFC) has been established in patients with treatment-resistant depression (TRD), suggesting that alterations in signal propagation from the left dlPFC to other brain regions may be linked to the pathophysiology of TRD. Alterations at the cellular level, including dysfunction of oligodendrocytes, may contribute to these network abnormalities. The objectives of the present study were to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…2019 ). In the present study, the ratio of the TRD group to the HC group was set to 2:1, in line with our previously published work ( Wada et al. 2022 ).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…2019 ). In the present study, the ratio of the TRD group to the HC group was set to 2:1, in line with our previously published work ( Wada et al. 2022 ).…”
Section: Methodsmentioning
confidence: 94%
“…In TRD, the DLPFC is not only the hub of cognitive functions, including executive function and working memory in normal physiology, but abnormalities in networks originating from this region have also been identified as the pathological basis of depression ( Wada et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DLPFC is responsible for top-down regulation of emotional processing, decision making, working memory, and attention processing, and is closely related to the onset of MDD [ 29 , 30 , 31 , 32 ]. DLPFC is an important target for repetitive transcranial magnetic stimulation in the treatment of TRD and is effective in preventing relapse in patients with TRD [ 33 , 34 ]. A study found that the male MDD patients had lower ALFF in the left superior frontal gyrus compared with female MDD patients, which supports the results of this study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the TMS coil was placed on the scalp at MNI coordinates [x = −38, y = 44, z = 26] at a 45 degree angle to the midline. Other details of the TMS-EEG experimental procedures have been reported in our previously published articles [16,17].…”
Section: Resting-state Eeg and Tms-eeg Measurement Methodsmentioning
confidence: 99%